Design Of A Finger Trainer Prototype For Paralyzed/Stroke Patients - Ammar Bin Azhar, Ammar (Universiti Teknologi Petronas, 2008)

(untitled)
This report introduces the background, objectives and literature review of the Finger Trainer for Paralyzed patients project as well as the methodologies in carrying out the project. The aim of the project is to come out with a prototype of a finger trainer machine used to facilitate patients in the rehabilitation program. This trainer is designed to be compact, portable and could be operated with minimum supervision from therapists. Stroke defined as a cardiovascular disease that designates the rapid loss of brain function due to an interruption in the blood supply to all or part of the brain [1], has became a big concern in the medical field as it has contributed to a big portion to the cause of death in the world including Malaysia [2]. Various types of treatments are available including the post-stroke rehabilitation process [3]. This project is an aid to ease the process of the physiotherapy programs and to reduce the involvement of third parties i.e. physiotherapists, nurses and trainers during the rehabilitation training period. This project was initiated due to the high demands of physiotherapy programs worldwide as it has became a large threat towards the health of the people all over the globe [4]. This was taking into account the insufficient amount of trainers and physiotherapists to cater this mass disease. The finger trainer will adapt the post-stroke approach using the Continuous Passive Motion (CPM) concept. It works as a medium that trains and teaches the finger nerves of its movements [5]. Simple mechanical and electrical assemblies are used in this machine to reduce the cost without having to lose the main functions of the machine.